The book of kings ebook The book of kings: mister max 3. - Voigt, Cynthia (Mister Max, 2015)
In Act III of Newbery Medalist Cynthia Voigt’s Mister Max trilogy, the solutioneer sets off to rescue his missing parents!   Ever since Max’s parents were spirited away on a mysterious ship, he has longed to find them.   He’s solved case after case for other people in his business as “solutioneer.” And he’s puzzled out the coded messages sent by his father. He doesn’t know exactly what’s happened, but he knows his parents are in danger—and it’s up to Max to save them.   Max and his friends (and a few old foes) don disguises and set sail on a rescue mission. It will take all of Max’s cleverness and daring to outmaneuver the villains that lie in wait: power-hungry aristocrats, snake-handling assassins, and bombardier pastry chefs. And behind the scenes, a master solutioneer is pulling all the strings.... Has Max finally met his match?   “Immensely appealing.” — The New York Times Book Review “A perfect read-aloud, the story will appeal to fans of fantasy, adventure, mystery, and humor.” —The Christian Science Monitor